(3OjhGf GdJdYaQjs - (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s ((3EOQjS Hf Ydj Hf EHQGgje Hf Ydj Hf QGTO GdMSfj s)
(3ChdgG (B:s
(3bGd GdTjN GdYGde jeOM Gdedc GdCTQa ehSi Hf Gdedc GdYGOd de CRd ecKQkG Ydjg dSDGdG hLhGHkG eG YfOg dj Shi dG s
(3BNQgG (B:s
(3ba fOY Edi Gddg JYGdi aYSi Cf jLeY HjffG ceG aQbfG GfJgi eG hLO ef cdGe GdJdYaQj QMeg Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B27 - (3U(B47s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B25s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B54 s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(2/369) s
Keywords: (3GdCOHs